Natural jute fiber treated with silane coupling agent KH570 reinforced polylactic acid composites: mechanical and thermal properties. Issue 21 (November 2022) - Fang, Cui-cui; Song, Xueyang; Zou, Ting; Li, Yuan-yuan; Wang, Ping; Zhang, Yan
With the progress of society, fiber reinforced composites have become the subject of research in the field of composite materials, in which natural fibers are widely used in the enhancement and modification of thermoplastics due to their low density, biodegradation and most wide origins. However, the hydrophilicity of special fiber is the main factor that hinders its bonding with hydrophobic polymer matrix which leads to poor interface compatibility between the fiber/matrix interface. The coupling agent can increase the nonpolarity of the natural fiber and the compatibility between the fiber and the resin. In this study, the composites were fabricated by the film stacking method, and the surface of jute fiber was treated with silane coupling agent so as to prepare jute/polylactic acid composites with good mechanical and thermal properties. The mechanical and thermomechanical results show that the combination of the coupling agent can significantly improve the interfacial bond of the jute/polylactic acid composites, leading to an efficient enhancement of comprehensive performance.